Langerhans cell histiocytosis mimicking otitis media - Ishak, Noor Liza; Tan, Sui Teng; Hassan, Nor Eyzawiah; Alias, Azila (Universiti Putra Malaysia, 2023)
Langerhans cell histiocytosis (LCH) is a spectrum of disease characterised by proliferation of Langerhans cells causing local or systemic manifestations. We report a two-year old boy who presented with a two-month history of progressive painless swelling over the right zygomatic region with ipsilateral otorrhea. Radiological investigation revealed an expansile hypodense lesion within the temporal bone with erosion of surrounding structures and meningeal enhancement. An ultrasound-guided biopsy of the lesion confirmed the diagnosis of LCH. LCH of the temporal bone may masquerade as otitis media with intra-temporal complications. A high index of suspicion is essential to avoid delay in diagnosis and management.